Professionalism of Technical Teacher in Vocational Education: : Professional Knowledge That Contribute To A Teacher’s Effectiveness - Sulaiman, Junita; Yunus, Faizal Amin Nur; Wan Ahmad, Wan Mohd Rashid (Online Journal for TVET Practitioners, 2019)
Abstract: Teachers are the key to the educational system where professional standards of teaching are used as a set of criteria in determining professionalism of technical teachers. Teachers’ professionalism and skills affect their students’ progress and are an important component of the TVET institution. A competent teacher is form of quality assurance for students’ learning. This study was conducted to generate an empirical evidence on the elements of professional knowledge that involves technical teachers in Malaysia Vocational College (VC). This study uses of quantitative method that involved data collection through the newly developed instrument of professional knowledge. A survey technique was used as the major method with the instrument on 300 technical teachers from Malaysia Vocational College (VC) around Malaysia. The results have shown that there were similarities and differences of the elements used by the teachers. There are several elements that shows highest score. Meanwhile, there is one element shows the lowest score in using the professional knowledge elements. In conclusion, this study shows the need of professional knowledge because it is an important aspect of strengthening the teacher’s professionalism in the development of technical and vocational teacher.